Parliamentary control of the Bundeswehr - Timo Noetzel; Benjamin Schreer (Stiftung Wissenschaft und Politik (SWP), 2007)
The right of the German Bundestag to have the final say on decisions to deploy German armed forces abroad is currently subject to intense political and public debate. Two central challenges for German security and defense policy are fundamental to this debate. Firstly, deployment decisions of this kind increasingly are being predetermined at the international level - within the respective frameworks of NATO and the EU - to such an extent that in reality there is very little room left for parliament if it is to avoid seriously abrogating Germany's alliance responsibilities. Secondly, emerging security threats have led to closer integration of national security institutions and actors and this in turn requires an adaptation of structures of parliamentary control. How should parliament respond to these developments?
Keywords: 320